Traditional medicines and their common uses in central region of Syria: Hama and Homs - an ethnomedicinal survey - Chadi Khatib; Abdulhakim Nattouf; Mohamad Isam Hasan Agha (Taylor & Francis Group, 2021)
Context Since ancient times, traditional Arabic medicine (TAM) has been used to treat various diseases in Syria. They are cost-effective with fewer side effects and are more suitable for long-term use compared with chemically synthesized medicines. In addition, the scientific importance is manifested, as this survey proceeds, for the purposes of verifying and documenting these traditional medicines and their common uses. Objective We conducted ethnobotanical and ethnomedicine research on plants traditionally used to treat various diseases in central region of Syria. Methods Information was collected from 2019 to 2021 from the cities of Homs and Hama and their villages, which are two governorates located in central Syria, after interviews with traditional practitioners called Attarin, and many other people. Plant specimens were collected according to different references concerning medicinal plants of Syria, to document the traditional uses of plants at least two of the traditional healers and three other people were asked. Results In this survey, we listed 76 medicinal plants belonging to 39 families in alphabetical order with the parts used and the method of preparation according to their therapeutic use, which are used to treat 106 ailments. Conclusions Many of the uses of medicinal plants mentioned in this survey are still under study. There is no doubt that this study will provide new data that could contribute to further pharmacological discoveries by identifying the active ingredients and their mechanism of effect by doing additional pharmacological work to confirm the alleged biological activities of these plants.